2022
DOI: 10.1088/2053-1583/ac88e2
|View full text |Cite
|
Sign up to set email alerts
|

Ti3C2T x MXene anchoring semi-metallic selenium atoms: self-powered photoelectrochemical-type photodetector, hydrogen evolution, and gas-sensing applications

Abstract: MXenes have demonstrated substantial promise as photocatalysts and electrocatalysts for a variety of applications such as self-powered photoelectrochemical (PEC)-type photodetector, hydrogen evolution reaction (HER), and vapor sensing applications. However, their mechanism is still poorly figured out. Currently, Ti3C2Tx MXene suffers from low photoresponsivity, high overpotential, and low sensitivity in such important applications. In order to develop catalytic activity and performances of those devices, modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…4a-c). 33 It can be observed that the responsivity of the Te/Ti 3 C 2 T x sample (Fig. 5a) reaches 70 μA W −1 which is almost 20 times higher than the responsivity of blank few-layered Ti 3 C 2 T x (Fig.…”
Section: Pec Photodetectormentioning
confidence: 85%
See 1 more Smart Citation
“…4a-c). 33 It can be observed that the responsivity of the Te/Ti 3 C 2 T x sample (Fig. 5a) reaches 70 μA W −1 which is almost 20 times higher than the responsivity of blank few-layered Ti 3 C 2 T x (Fig.…”
Section: Pec Photodetectormentioning
confidence: 85%
“…Similar results have been observed in single Se atoms on Ti 3 C 2 T x MXene nanosheets under CO 2 conditions, 26 as well as in our other recent work by the solid-state annealing method. 33 This variation would be due to the substitution in termination contents by chalcogen elements and oxygen-containing terminations (like Ti–O, C–O, S–O, and Se–O). High-resolution XPS spectra of the elements of the samples can further help evaluate the changes in chemical states and their occupancy after decoration of the few-layered Ti 3 C 2 T x MXene with Te, Se, and S (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[21] The formation of a greater TiO 2 anatase phase in Te/Ti 3 C 2 T x is due to oxygen-containing species and a fraction of fluorine surface terminations on Ti 3 C 2 T x , which are well-known for stabilizing TiO 2 anatase. [29,34] Raman characterizations show that the vibrational modes of Ti 3 C 2 T x are at three main bonds of A 1g (Ti atoms at ≈210 cm −1 , TiO 2 at ≈500 cm −1 , C atoms at ≈625 cm −1 , and C─C at ≈700 cm −1 ), E g (TiO 2 at ≈130 cm −1 , O atoms, ≈376 cm −1 ) and H atoms at ≈255 cm −1 . An additional band in the Te/Ti 3 C 2 T x sample was detected, attributed to the vibration and translational modes of the Te (A 1g at ≈120 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[68] For instance, the properties shown by 2D semiconductors are yet interesting for an increasingly large market slice, and despite all the aforementioned challenges, preparing and manipulating high-quality 2D materials is still developing. [13,68] Chemically 2D materials present a wide range of categorizes of oxides, [69][70][71] carbon-based, [61,72,73] element-based (borophene, [74,75] black phosphorus, [48] silicene, [76,77] germanene, [78,79] antimonene, [56,80] stanene, [79,[81][82][83][84] ), carbides and nitrides of transition metal (MXenes, [85,86] ) and metal chalcogenides. In the case of the last family of 2D materials, the most studied are the transition metal dichalcogenides (MoS 2 , [62,64] WS 2 , WSe 2 , and WTe 2 [87] ) and the various group of III-V, [88] and III-VI chalcogenides.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically 2D materials present a wide range of categorizes of oxides, [ 69–71 ] carbon‐based, [ 61,72,73 ] element‐based (borophene, [ 74,75 ] black phosphorus, [ 48 ] silicene, [ 76,77 ] germanene, [ 78,79 ] antimonene, [ 56,80 ] stanene, [ 79,81–84 ] ), carbides and nitrides of transition metal (MXenes, [ 85,86 ] ) and metal chalcogenides. In the case of the last family of 2D materials, the most studied are the transition metal dichalcogenides (MoS 2 , [ 62,64 ] WS 2 , WSe 2 , and WTe 2 [ 87 ] ) and the various group of III‐V, [ 88 ] and III‐VI chalcogenides.…”
Section: Introductionmentioning
confidence: 99%